Pengelolaan terbitan berseri di Perpustakaan Museum Bala Putradewa - Intan Winarti (UIN Sumatera Utara, 2019)
Series publications are sources available in the library. These information sources have up-to-date and updated information on various topics of discussion that are used as sources of reference science for research of students and lecturers. Serial issue is one of the library collections which are mostly unprocessed and utilized. In this paper, we discuss about serial publications in the Bala Putradewa Museum library, including journals, newspapers or newspapers, bulletins, magazines and others. In the library of Bala Putradewa Museum, most public collections are not collections related to history. This confession is still very minimal for updated information to be consumed by visitors, the visitors are almost non-existent every day. Preservation of publications in the library Museum Balaputra still uses manual methods because of the absence of a special budget. Development of collections was not carried out due to the absence of a budget. On average, collections in the old Putadewa Bala Museum and many collections have been lost and damaged. So in the library of the Museum of Bala Putradewa all still use the manual system because of the lack of attention from the leadership and the staff themselves. Keyword: special libraries, serial publications, management